Development and characterization of sulfonated poly (ether ether ketone) membrane for direct methanol fuelcell application [electronic resource] - Juhana Jaafar, 1981- (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Gas)) - Universiti Teknologi Malaysia, 2006